Perlocutionary Act Analysis in the Indonesia Version of Tesla Electric Car Advertisement Video - Siti Musarrofah (Universitas Muhammadiyah Barru, 2023)
The problems of this study are how the perlocutionary speech act of electric car is advertised and how to deliver the car advertisements. Thus this research will further improve students’ language skills. This research uses a qualitative descriptive approach for the Indonesian version of the electric car promotional video by Prestige Motorcars Indonesia. Data collection techniques used were listening and taking notes. The listening technique in question is listening to the speech contained in the car advertisement in the video and the note-taking technique in question is recording the results of the speech contained in the Tesla electric appliance advertisement on YouTube. The equivalent of the method, which is a means to determine whether the language is outside, separate, and not part of the language in question. While the method of presenting the results of the analysis uses an informal method because the data is in the form of speech. Based on the analysis of perlocutionary speech acts in the Indonesian version of the Tesla electric car promotional video by Prestige Motorcars Indonesia, there are direct perlocutionary speech acts that refer to aspects of sentence meaning; meaning of speech, mode of speech act.